Drug level testing as a strategy to determine eligibility for drug resistance testing after failure of ART: a retrospective analysis of South African adult patients on second‐line ART. Issue 6 (9th June 2020) - Hermans, Lucas E; Steegen, Kim; ter Heine, Rob; Schuurman, Rob; Tempelman, Hugo A; Moraba, Robert; van Maarseveen, Erik; Nijhuis, Monique; Pillay, Taryn; Legg‐E'Silva, Derryn; Snyman, Tracy; Schapiro, Jonathan M; et al.
Abstract : Introduction: When protease inhibitor (PI)‐based second‐line ART fails, guidelines recommend drug resistance testing and individualized third‐line treatment. However, PI‐resistant viral strains are rare and drug resistance testing is costly. We investigated whether less costly PI‐exposure testing can be used to select those patients who would benefit most from drug resistance testing. Methods: We performed a retrospective analysis of South African adults living with HIV experiencing failure of ritonavir‐boosted‐lopinavir (LPV/r)‐based second‐line ART for whom drug resistance testing results were available. We included patients who received plasma‐based drug resistance testing at a central South African reference laboratory in 2017 and patients who received dried blood spots (DBS)‐based drug resistance testing at a rural South African clinic between 2009 and 2017. PI‐exposure testing was performed on remnant plasma or DBS using liquid chromatography mass spectrometry (LCMS). Additionally, a low‐cost immunoassay was used on plasma. Population genotypic drug resistance testing of the pol region was performed on plasma and DBS using standard clinical protocols. Results: Samples from 544 patients (494 plasma samples and 50 DBS) were included. Median age was 41.0 years (IQR: 33.3 to 48.5) and 58.6% were women. Median HIV‐RNA load was 4.9 log10 copies/mL (4.3 to 5.4). Prevalence of resistance to the NRTI‐backbone was 70.6% (349/494) in plasma samples and 56.0% (28/50) in DBS. Major PI‐resistance mutations conferring high‐level resistance to LPV/r were observed in 26.7% (132/494) of plasma samples and 12% (6/50) of DBS. PI‐exposure testing revealed undetectable LPV levels in 47.0% (232/494) of plasma samples and in 60.0% (30/50) of DBS. In pooled analysis of plasma and DBS samples, detectable LPV levels had a sensitivity of 90% (84% to 94%) and a negative predictive failure of 95% (91% to 97%) for the presence of major LPV/r resistance. Conclusions: PI‐exposure testing revealed non‐adherence in half of patients experiencing failure on second‐line ART and accurately predicted the presence or absence of clinically relevant PI resistance. PI‐exposure testing constitutes a novel screening strategy in patients with virological failure of ART that can differentiate between different underlying causes of therapy failure and may allow for more effective use of limited resources available for drug resistance testing.